Hubungan Penerapan Strategi Pembelajaran Berbasis Masalah Oleh Guru Geografi pada Materi Bumi dan Jagad Raya dengan Hasil Belajar Siswa Kelas X SMA Negeri 10 Singkawang Tahun Ajaran 2012/2013 - Ivan Veriansyah (Jurnal PIPSI (Jurnal Pendidikan IPS Indonesia), 2016)
This research aims to know the objective information about (1) the application of problem-based learning strategy about earth and solar system material of tenth grade students of SMA 10 Singkawang (2) students’ achievement about earth and solar system material of tenth grade students of SMA 10 Singkawang (3) the correlation between problem based learning strategy about earth and solar system material with the students’ achievement of tenth grade students of SMA 10 Singkawang.This research is quantitative research and uses correlation study method. The populations in this research are all the social tenth grade students which consist of 133 students and the samples are 53 students by using random sampling proportional technique. The technique of collecting the data is indirect observations and indirect communication. The tools of data collection are questionnaire and interview sheet. The data analysis technique in this research is using product moment correlation formula.The result of the research shows that (1) the application of problem based learning strategy about earth and solar system material of tenth grade students of SMA 10 Singkawang is “very good” with percentage 90,07%; (2) the average score of students’ achievement about earth and solar system material of tenth grade students of SMA 10 Singkawang is 78,58 and categorize as “good”; (3) there is a significant and positive correlation between problem based learning strategy about earth and solar system material with the students’ achievement of tenth grade students of SMA 10 Singkawang and the r is 0,7549 and categorize as “strong”.